PENGGUNAAN METODE CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK PENINGKATAN HASIL BELAJAR KETERAMPILAN ANYAMAN SISWA KELAS VIII 9 DI SMPN 18 PADANG - ZUFRI YENNI, Drs. Abd. Hafiz, M.Pd, Dr. Budiwirman, M.Pd (Serupa The Journal of Art Education, 2013)
This study aims to determine the improvement of student learning outcomes for subjects woven skills in eighth grade 9 SMP Negeri 18 Padang used the Contextual Teaching And Learning (CTL). The data in this study were collected using the research instruments and observation sheets. To see the change in students' learning activities in the two cycles are cycles I and II. The study involved students of class VIII 9, 28 in total. Data obtained and analyzed using percentages. The study findings suggest that the increase in learning outcomes significantly webbing skills, it can be seen from the average pre-cycle 69.07 to 71.85 at the first meeting of the first cycle, the ability of students continue to show improvement in the second meeting with the average 74.74. At the first meeting of the second cycle also showed an average increase of 80.26, the second meeting of the ability of students continue to show improvement with an average of 81.08. It can be concluded that the method of Contextual Teaching And Learning (CTL) can improve learning outcomes woven skills Eighth Grade 9 students at Junior High School 18 Padang. Key words: Contextual the Teaching and Learning (CTL) Method, in Improving the Learning autcome. In the Webbing Subject or Grade VIII 9 in SMP Negeri Padang.